Inhibition of the activin receptor signaling pathway: A novel intervention against osteosarcoma. (12th November 2020) - Meier, Daniela; Lodberg, Andreas; Gvozdenovic, Ana; Pellegrini, Giovanni; Neklyudova, Olga; Born, Walter; Fuchs, Bruno; Eijken, Marco; M. Botter, Sander
Abstract: Osteosarcoma is a cancer of pathological bone remodeling with high mortality and severe comorbidity. New therapies are urgently needed. Activin A, a member of the transforming growth factor β (TGFβ) superfamily, has been suggested to stimulate proliferation and invasion of osteosarcoma cells in vitro, thus representing a potential therapeutic target. In this study, inhibition of the activin receptor signaling pathway was explored as a therapy for osteosarcoma. In a murine intratibial osteosarcoma xenograft model, two types of inhibitors were tested: (a) a soluble activin type IIA decoy receptor (ActRIIA‐mFc), or (b) a modified variant of follistatin (FSTΔHBS ‐hFc), either alone or in combination with a bisphosphonate. Both inhibitors reduced primary tumor development by nearly 50% compared to vehicle treatment. When ActRIIA‐mFc was combined with bisphosphonate, the effect on tumor size became even more pronounced (78% reduction vs. vehicle). Moreover, FSTΔHBS ‐hFc increased body weight in the face of tumor progression (14% increase vs. vehicle), and ActRIIA‐mFc reduced the number of lung metastases when combined with bisphosphonate. The present study demonstrates a novel approach to treating osteosarcoma and encourages further investigation of inhibition of the activin receptor signaling pathway as an intervention against the disease. Abstract : Inhibition of the activin receptor signaling pathway reduces tumor volume, pathological bone remodeling, and counteracts the cachexia that follows in the wake of osteosarcoma.